School-Based Intervention in Reducing Sugar-Sweetened Beverage Consumption Among Children and Adolescents: A Systematic Literature Review - Zahra Ayu Qalbina; Tri Krianto (Universitas Pahlawan Tuanku Tambusai, 2026)
Sugar-sweetened beverages (SSB) consumption in Indonesia has increased, contributing to the prevalence of obesity and cardiometabolic diseases. Schools represent a strategic setting to promote healthy lifestyles among children and adolescents. This study aimed to review school-based interventions for reducing SSB consumption and to identify their limitations and recommendations. A systematic literature review was conducted in accordance with PRISMA guidelines. Articles published between 2015 and 2025 were retrieved from PubMed, Scopus, and ProQuest. From an initial 705 articles, 8 studies met the eligibility criteria for inclusion. The findings revealed that most interventions utilized a combination of educational and environmental strategies, while others employed peer-influence or environmental-only approaches. Integrated approaches that addressed both educational and environmental strategies were generally associated with more favorable outcomes. Nevertheless, several limitations were identified, particularly those related to challenges in establishing causal inference and the potential for measurement bias. For further research, it is advised to adopt a participatory design approach, integrate interventions into school curriculum and policy framework, and improve both physical and social access to drinking water within the school environment.